The Patient-Reported Outcome (PRO) Consortium: Lessons Learned Along the Path to PRO Instrument Qualification. (January 2015) - Hayes, Risa P.; Blum, Steven I.; Gordon, Mark Forrest; Piault, Elisabeth; Burke, Laurie B.; Slagle, Ashley F.; Coons, Stephen Joel
Established in 2008, the Patient-Reported Outcome (PRO) Consortium is a collaboration among the US Food and Drug Administration's Center for Drug Evaluation and Research, the Critical Path Institute, the pharmaceutical/biotechnology industry, and other stakeholders. The purpose of the consortium is to qualify PRO instruments through the Center for Drug Evaluation and Research's drug development tool qualification process for use as clinical trial endpoints to support drug approval and product labeling claims. The PRO Consortium has made notable progress toward collaborative development of PRO instruments in the following areas: asthma, mild cognitive impairment, depression, functional dyspepsia, irritable bowel syndrome, non–small cell lung cancer, and rheumatoid arthritis. This progress has come with considerable challenges, including navigating a new and evolving regulatory initiative, gaining consensus on key issues, and maintaining communication and engagement in a precompetitive environment. The purpose of this paper is to describe some of the challenges and lessons learned since the creation of the PRO Consortium in hopes that this information may provide direction and insight for similar collaborations.